2013
DOI: 10.12720/jolst.1.1.89-93
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Azadirachta Indica Against Alternaria Solani

Abstract: The antifungal activity of Azadirachta indica L was investigated against Alternaria solani. sorauer responsible for early blight in potato. Different concentrations of leaf and fruit methanol extracts viz. 1%, 2%…5% were applied against A. solani. Leaf extract was found more significant than fruit extract. This extract was subjected to bioassays guided fractionation by using various organic solvents viz. n-hexane, chloroform, ethyl acetate and n-butanol. In vitro antifungal activities of these fractions were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…indica essential oils (Somda, Leth, & Sereme, ). Among various extracts, ethyl acetate extracts of leaves and fruits showed maximum fungicidal activity against Alternaria solani followed by methanolic extract (Jabeen, ). Ethanolic extracts of leaves and seed oil were applied to control brown spot disease of rice caused by Cochliobolus miyabeanus .…”
Section: Pharmacological Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…indica essential oils (Somda, Leth, & Sereme, ). Among various extracts, ethyl acetate extracts of leaves and fruits showed maximum fungicidal activity against Alternaria solani followed by methanolic extract (Jabeen, ). Ethanolic extracts of leaves and seed oil were applied to control brown spot disease of rice caused by Cochliobolus miyabeanus .…”
Section: Pharmacological Attributesmentioning
confidence: 99%
“…alternata species (Paul & Sharma, 2002;Vir & Sharma, 1985). Moderate antifungal activity was observed for oil extract against Aspergillus fumigatus and Aspergillus niger when studied using disc diffusion method (Bansod & Rai, 2008 of leaves and fruits showed maximum fungicidal activity against Alternaria solani followed by methanolic extract (Jabeen, 2013 (Suleiman, 2011). Dry seed extracts of the tree also showed complete inhibition of F. oxysporum growth at different concentrations (Agbenin & Marley, 2006).…”
Section: Antifungal Activitymentioning
confidence: 99%
“…Aqueous extracts of various parts of neem such as neem oil and its chief principles have antifungal activities and have been reported by earlier investigators [ 18,19]. A study was undertaken to examine the antifungal activity of Azadirachta indica L. against Alternaria solani Sorauer and results confirmed that ethyl acetate fraction was found most effective in retarding fungal growth with MIC of 0.19 mg and this fraction was also effective than fungicide (metalaxyl + mancozeb) as the fungicide has MIC of 0.78mg [20]. It was also observed that the mature leaf (7-9 days old) extracts have more inhibitory effect than that of young (2-4 days old) one.…”
Section: Discussionmentioning
confidence: 58%
“…Control media was without plant extract. Three replicates were made for each concentration and fungal inoculums were added in each plate of each concentration (Jabeen et al, 2013). n-hexane fraction was selected for GC-MS analysis due to significant antifungal potential in the previous assay.…”
Section: Methodsmentioning
confidence: 99%